Emerging clinical and research approaches in targeted therapies for high-risk neuroblastoma - Albatool AlKhazal; Samiha Chohan; Samiha Chohan; Destani J. Ross; Jinhwan Kim; Jinhwan Kim; Erin G. Brown (Frontiers in Oncology)
Neuroblastoma is a pediatric cancer that originates from neural crest cells and is the most common extracranial solid tumor in children under five years of age. While low-risk neuroblastoma often regresses spontaneously, high-risk neuroblastoma poses a significant clinical challenge. Recent advances in understanding neuroblastoma’s molecular mechanisms have led to the development of targeted therapies that aim to selectively inhibit specific pathways involved in tumor growth and progression, improving patient outcomes while minimizing side effects. This review provides a comprehensive review of neuroblastoma biology and emerging therapeutic strategies. Key topics include (a) immunotherapies and immunotargets, (b) non-coding RNAs (long non-coding RNA, microRNA, and circular RNA), (c) molecular biomarkers and pathways, and (d) limitations and future directions.